Konsep Bagi Hasil Bidang Industri dalam Ekonomi Islam - Putria, Uus; Nasrudin, Nasrudin; Nursari, Nina (STAI Siliwangi Bandung, 2020)
Collaboration is an activity that is familiar to human beings. Cooperation is a demand as an implication of the limitations in human beings, both limited property, abilities, physical, energy, and other human potential. With these limitations, humans are required to depend on other people to complete and help these limitations.Commercial activities in the Islamic conception of profit-oriented is free from usury. The concept of profit sharing in Islamic economics is applied in the industrial sector which is halal and avoids forbidden practices and prohibited by Islam. The advantage of this concept will give justice to both the owner and the employee. Thus the spirit of business will increase. In this case, it will discuss the concept of profit sharing in the industrial sector which uses mudharabah and musyarakah contracts.